RADI-10. THERAPEUTIC EFFECTS OF fSRS IN 44 CASES OF BRAIN METASTASES OF NSCLC WITH A MAXIMUM DIAMETER ≥ 4CM AND ANALYSIS OF ITS PROGNOSTIC FACTORS. (12th August 2019) - Mingyao, Lai; Zhen, Junjie; Li, Juan; Zhou, Jiangfen; Hu, Qingjun; Ye, Minting; Li, Shaoqun; Xiao, Xiao; Wang, Lichao
Abstract: OBJECTIVE: To analyze the therapeutic effects of fSRS on brain metastases of NSCLC with a maximum diameter ≥ 4 cm, and explore the prognostic factors. METHODS: A retrospective analysis was conducted on the clinical data of 44 cases of brain metastases of NSCLC with a maximum diameter ≥ 4 cm in Guangdong Sanjiu Brain Hospital from January 2006 to December 2016. RANO criteria were adopted for imaging evaluation at 3 months after completion of radiotherapy. One- and 2-year survival rates were calculated and the differences in survival rates between groups were analyzed with Log-rank test. Kaplan-Meier method was used in univariate analysis to investigate the effects of KPS, RPA classification, number of metastases, total lesion volume, systemic treatment and surgery on prognosis; and Cox regression model in multivariate analysis. RESULTS: The postoperative imaging evaluation showed that there were 5 cases of CR, 20 of PR, 12 of SD and 7 of PD. The median PFS, OS, 1- and 2-year survival rates were 6 months, 16 months, 65.9% and 20.5%, respectively. KPS, RPA classification, number of metastases and surgery had no significant correlations with prognosis. However, systemic treatment and the maximum lesion volume ＜28.3cc were considered as favorable factors related to prognosis (P=0.046, 0.027). Moreover, the maximum lesion volume ＜28.3cc was found to be the independent prognostic factor for the survival (P=0.035). CONCLUSION: Treatment of brain metastases of NSCLC with a maximal diameter ≥4 cm with fSRS is proved to be feasible. The maximum lesion volume is related to prognosis. Systemic treatment (chemotherapy, TKI treatment, etc.) may improve prognosis, but more cases are needed to investigate the prognostic significance.